Upaya Meningkatkan Motivasi Belajar Bahasa Indonesia melalui Pemberian Penguatan (Reinforcement) pada Siswa Kelas IV SD Muhammadiyah 3 Kuala Beringin - Siahaan, Ucok; Doly Nasution, Marah (STKIP Subang, 2026)
This Classroom Action Research (CAR) was motivated by the finding of a learning motivation crisis that resulted in low participation and passivity among 25 students of grade IV at SD Muhammadiyah 3 Kuala Beringin in learning the Indonesian Language. This condition hindered the development of students' reading, speaking, writing, and listening skills. This study aimed to improve students' learning motivation through the application of Reinforcement Techniques focused on a combination of specific verbal reinforcement and a token economy in the form of active stickers. The research was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. Data collection was carried out exclusively using observation techniques through a learning motivation observation sheet. The success indicator was set at 75% of the total students reaching a minimum scale of